2006
DOI: 10.2106/jbjs.e.01042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radial and Ulnar Torsion Profiles with Cross-Sectional Magnetic Resonance Imaging

Abstract: Cross-sectional magnetic resonance imaging is currently the only available method to quantify rotational malunion of the radius and ulna. Its low side-to-side reliability warrants comparison between the imaging results and the clinical findings. A side-to-side difference in the rotation profile may serve as a reason to perform an axial osteotomy when the results of the clinical and magnetic resonance imaging assessments are consistent with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
0
27
1
Order By: Relevance
“…Previous studies have shown a wide variation in the absolute values of the radial torsion angle, resulting in a very wide range of normal values 6,7. The parameters adopted in the present study for the measurement of the radial torsion angle differed from those employed in other studies, resulting in considerably different absolute values compared to previously reported data but a substantially lower variation between sides for both denuded bones and volunteers.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous studies have shown a wide variation in the absolute values of the radial torsion angle, resulting in a very wide range of normal values 6,7. The parameters adopted in the present study for the measurement of the radial torsion angle differed from those employed in other studies, resulting in considerably different absolute values compared to previously reported data but a substantially lower variation between sides for both denuded bones and volunteers.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, none of the existing methods is sufficiently accurate to identify rotational deviations of the radius of less than 35°. However, rotational deviations less than 35° have been described as important in the reduction of forearm rotation 7,9-12. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angular deformities are assessed on true AP and lateral views. Rotational deformities are more difficult to assess and require assessment of the relationship between the radial styloid and bicipital tuberosity and ulnar styloid and coronoid process on full forearm views comparing both sides [2, 12]. The level of axial malunion may be defined by comparison with the level of the original fracture or the level of angular deformity in patients with combined deformity.
Fig.
…”
Section: Clinical Presentationmentioning
confidence: 99%